2021
DOI: 10.1002/spy2.182
|View full text |Cite
|
Sign up to set email alerts
|

Finite state machine for cloud forensic readiness as a service (CFRaaS) events

Abstract: The importance of demonstrating the correctness of forensic analysis tools and automated incident management tools reinforces the need for a finite state machine (FSM) engine that can generate automated forensic processes. Hence, in this paper, we present an event-based FSM representation for Cloud Forensic Readiness as a Service (CFRaaS), where we also show how the FSM's predetermined states and transitions could be used to formulate an automated forensic process and generate a hypothesis for litigation purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Various studies have been reported that investigate and recognize cybercrime [22,[31][32][33][34][35][36][37][38][39][40], data cracks [23,[41][42][43][44][45][46][47][48][49][50], and other digital risks [24,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: A Related Workmentioning
confidence: 99%
“…Various studies have been reported that investigate and recognize cybercrime [22,[31][32][33][34][35][36][37][38][39][40], data cracks [23,[41][42][43][44][45][46][47][48][49][50], and other digital risks [24,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: A Related Workmentioning
confidence: 99%
“…A Finite State Machine (FSM) is depicted as a graph with nodes [39] in which it is possible to give computations of a number of states and transitions for some given inputs and output conditions, respectively [40], as shown in Figure 3. Definition 2.…”
Section: Finite State Machinementioning
confidence: 99%
“…However, digital evidence in ICS can be volatile, as control devices typically feature low storage resources and can be damaged by attacks ( Van Vliet et al, 2015 ). ICS therefore need to be Forensic-Ready ( Kebande and Choo, 2022;Rowlingson, 2004;Zainudin et al, 2022 ), i.e., capable of identifying, collecting, and preserving, in advance , data that may be used as evidence to investigate potential, known incidents ( Alrajeh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%